2014
DOI: 10.3892/ijmm.2014.2001
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic analyses of a novel cytokine, interleukin-34 and its potential role in cancer prediction

Abstract: Interleukin-34 (IL-34) is a novel cytokine, which is composed of 222 amino acids and forms homodimers. It binds to the macrophage colony-stimulating factor (M-CSF) receptor and plays an important role in innate immunity and inflammatory processes. In the present study, we identified the completed IL-34 gene in 25 various mammalian genomes and found that IL-34 existed in all types of vertebrates, including fish, amphibians, birds and mammals. These species have a similar 7 exon/6 intron gene organization. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…Importantly, the increased IL‐34 was associated with liver inflammation and fibrosis in HBV infection, and the results were consistent with the phenomenon observed in non‐alcoholic fatty liver disease and chronic hepatitis C . Besides these, IL‐34 is shown to increase in different tumour cells, and related to the prognosis of various cancers. In addition, Zhou S et al showed that the upregulation of IL‐34 contributed the development of HCC .…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, the increased IL‐34 was associated with liver inflammation and fibrosis in HBV infection, and the results were consistent with the phenomenon observed in non‐alcoholic fatty liver disease and chronic hepatitis C . Besides these, IL‐34 is shown to increase in different tumour cells, and related to the prognosis of various cancers. In addition, Zhou S et al showed that the upregulation of IL‐34 contributed the development of HCC .…”
Section: Discussionsupporting
confidence: 83%
“…Regarding IL-34, emerging data also demonstrate its correlation with poor prognosis in several cancers, such as osteosarcoma and lung and breast cancer ( Fig. 3; Baghdadi et al, 2018;Wang et al, 2015). Expressed by various types of cancer cells and further induced upon chemotherapy treatment (Baghdadi et al, 2016;Baud'Huin et al, 2010;Cioce et al, 2014;Franzè et al, 2017;Wang et al, 2015), IL-34 binds to CSF-1R on mononuclear phagocytes, which play distinct roles during different stages of tumor progression (Baud'Huin et al, 2010;Noy and Pollard, 2014;Ségaliny et al, 2015c;Zins et al, 2018).…”
Section: Il-34 In Cancermentioning
confidence: 99%
“…Ensembl (http://www.ensembl.org/index.html) and the NCBI's Database of SNPs (http://www.ncbi.nlm.nih. gov/snp/) were used to obtain functionally relevant SNPs of the human IL-36RN gene as previously described (24,27,28). The SNPs that could disrupt exonic splicing enhancer (ESE)/exonic splicing silencer (ESS) motifs or cause a missense mutation were identified.…”
Section: Comparative Proteomic Analysis Of the Il-36rn Proteinmentioning
confidence: 99%